2020
DOI: 10.1002/pmrj.12407
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of a New Toileting Assessment Form for Patients with Hemiparetic Stroke

Abstract: Background Acquiring toileting independence is an important target of stroke rehabilitation. In planning an intervention for acquiring toileting independence, developing an assessment for individual subtasks that comprise toileting would assist in identifying specific tasks that prevent independence in patients and would facilitate interventions to improve toileting independence. Objective To examine the reliability and validity of a newly developed toileting assessment form, the Toileting Tasks Assessment For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
(12 reference statements)
5
9
0
Order By: Relevance
“…Previous studies reported the minimum weighted kappa coe cient value for inter-rater reliability of the TPAT to be the same as that of the TTAF (.61) [18,19]. For intra-rater reliability, minimum weighted kappa coe cient values were reported at .83 [18] and .60 [19] for the TPAT and the TTAF, respectively, similar to those in this study. They also reported Cronbach's alpha values of .97 for the TPAT [18] and .95 or .94 for the TTAF [19], which are also similar to the current results.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Previous studies reported the minimum weighted kappa coe cient value for inter-rater reliability of the TPAT to be the same as that of the TTAF (.61) [18,19]. For intra-rater reliability, minimum weighted kappa coe cient values were reported at .83 [18] and .60 [19] for the TPAT and the TTAF, respectively, similar to those in this study. They also reported Cronbach's alpha values of .97 for the TPAT [18] and .95 or .94 for the TTAF [19], which are also similar to the current results.…”
Section: Discussionsupporting
confidence: 84%
“…However, these instruments do not provide a breakdown of the individual component activities comprising toileting behaviour and indicating poor responsiveness [18]. These component activities include putting on and taking off pants, wiping the buttocks, and tearing off toilet paper [19,20]. An assessment of the individual components of each daily activity has been shown to be effective for determining rehabilitation goals and treatment planning [19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations